BLACKING CRITICISM: THROUGH AN EXPERIENCE FROM THE OUTSIDE (Muitas Vozes, 2024)
The proposed article has as its central objective to blacken literary criticism and, along with it, the experience of the outside. For this movement, it is necessary to decolonize the “outside” as it was thought in Western, Eurocentric molds and to decolonize criticism, which is white, cis and heterosexual. As theoretical-epistemological contributions, we will bring the black literature of Conceição Evaristo (1996) and black feminism to tension canonical criticism, the authorized discourse of white supremacy, imperial and patriarchal. We will take the risk and think of the crossroads as an experience of the outside or as a machinic-political agency of the black people. We will propose lines of escapes, transits and displacements necessary to expand the semantics of criticism and legitimize the critical look, so that we, black subjects, can think about literary criticism and our multiple processes of subjectivation. One of the expected and expected results is that we, as black people, need to raise our voices so that our story can be told by black hands. Finally, it is concluded that we need to tension this criticism that originated from a discursive authorization regime, to potentiate new experiences from the outside and new processes of subjectivation, starting from ourselves, having black literature as our powerful crossroads of struggle and emancipation.